Recent Advances in Intraoperative Nerve Bioimaging: Fluorescence‐Guided Surgery for Nerve Preservation. Issue 1 (14th August 2020) - Chen, Ying; Zhang, Hongxin; Lei, Zuhai; Zhang, Fan
Abstract : Accidental transection or injury of nerves during surgeries leads to severe patient morbidity and lowers the life quality of patients. The current imaging modality for nerves, such as magnetic resonance imaging (MRI), computerized tomography (CT), and high‐resolution ultrasound, cannot provide real‐time guidance for surgeons during surgical operations. Previously, intraoperative nerve recognition mainly depended on the surgeon's experience. But now, optical imaging techniques that exploit fluorescent light enable the direct intraoperative visualization of the areas of interest on a surgical site, which has the potential to improve real‐time nerve identification during surgeries. Herein, a brief introduction is provided to the structure of peripheral nerve (PN) fiber and fluorescent probes for nerve labeling that are based on these features are summarized. Then, the recent progress in fluorescence‐guided surgeries for nerve preservation is systematically summarized. Finally, the challenges and future opportunities for in vivo real‐time nerve identification are discussed. Abstract : Intraoperative nerve damage or injury is unavoidable in some surgical procedures and has a significant adverse effect on patients. The emerging technique of fluorescence labeling of specific tissue can help with the visualization of nerves, making it possible to preserve vital nerves during surgery. Herein, recent advances in fluorescence‐guided surgery for nerve preservation are summarized.